Firearm access and adolescent health: Safety in numbers?. (August 2020) - Chung, Samantha H.; Biely, Christopher; Dudovitz, Rebecca
Abstract: Access to firearms and perceived unsafe school environments are associated with negative adolescent health outcomes. Whether widespread acceptance of firearms alters these associations, however, is unknown. To address this literature gap, we examined whether peer acceptance of firearms moderates associations between personal firearm access and health outcomes. In 2018–2019, we analyzed Wave I of the National Longitudinal Study of Adolescent to Adult Health (collected 1994–1995) to assess personal firearm access and school-level percentage of firearm access, using weighted multilevel analyses with interactions to determine associations among personal access, school-level percentage of access, and adolescent depression, suicidality, general health, and perceived school safety. Models controlled for age, sex, race, region, urbanicity, family structure, parental income and education level, school type, school size, and school quality. Results showed that personal firearm access was associated with depression (OR 1.20 p = 0.03), suicidal ideation (OR 1.73, p < 0.001), and perceiving school as unsafe (OR 1.59, p < 0.001). A higher school-level percentage of access, however, was associated with lower rather than higher odds of perceiving school as unsafe (OR 0.83, p = 0.003). With interaction terms included, the association between personal access and suicidal ideation was weaker when school-level access was more common. Similarly, the association between school-level access and poor general health was negative among students with personal access but positive among students with no access. These findings suggest firearm access is a complex social phenomenon. In a low-access environment, personal firearm access may signify a high-risk physical and mental state. In schools where access is common, however, personal access may signify social belonging, possibly mitigating some potential negative health effects. Although evidence that firearm access is harmful remains clear, local norms may have a substantial moderating impact. Highlights: We investigate how widespread firearm access relates to adolescent health. Personal firearm access is associated with poor health, depression, and suicide. However, this relationship is weaker in schools where firearm access is common. The relationship between adolescent firearm access and health may vary by context.